Social Loafing Dalam Mengerjakan Tugas Kelompok Ditinjau dari The Big Five Personality Traits pada Mahasiswa - Atikah, Atikah; Hariyadi, Sugeng (Intuisi : Jurnal Psikologi Ilmiah, 2019)
Abstrak. Salah satu sisi negatif tugas kelompok adalah adanya kecenderungan anggota kelompok untuk mengurangi usaha (social loafing). Social loafing terjadi karena berbagai faktor salah satu diantaranya adalah faktor kepribadian. Kepribadian bersifat unik dan konsisten sehingga dapat digunakan untuk membedakan antara individu satu dengan lainnya. Penelitian ini bertujuan untuk mengetahui adakah perbedaan social loafing dalam mengerjakan tugas kelompok ditinjau dari the big five personality traits pada mahasiswa UNNES. Penelitian ini merupakan penelitian komparasi. Sampel penelitian berjumlah 414 mahasiswa UNNES dengan teknik sampling yang digunakan adalah proportional stratified cluster random sampling. Data penelitian diambil menggunakan dua skala, yaitu skala social loafing yang terdiri dari 44 aitem valid dan skala adaptasi the big five inventory yang terdiri dari 59 aitem valid. Koefisien reliabilitas skala social loafing yaitu sebesar 0,883 dan koefisien reliabilitas pada tiap-tiap trait kepribadian sebesar 0,851 (extraversion), 0,737 (agreeableness), 0,853 (consccientiousness), 0,796 (neuroticism) dan 0,813 (opennes). Metode analisis data yang digunakan yaitu ANAVA satu arah. Hasil olah data menunjukan terdapat perbedaan social loafing ditinjau dari the big five personality traits. Analisis lebih lanjut menemukan, pertama ada perbedaan social loafing pada trait kepribadian extraversion dengan trait kepribadian neuroticism dengan signifikansi 0,000 (p<0,05). Kedua, ada perbedaan social loafing pada trait kepribadian extraversion dengan trait kepribadian opennes dengan signifikansi 0,006 (p<0,05). Ketiga, ada perbedaan social loafing pada trait kepribadian agreeableness dengan trait kepribadian conscientiousness dengan signifikansi 0,010 (p<0,05). Keempat, terdapat perbedaan social loafing pada trait kepribadian conscientiousness dengan trait kepribadian neuroticism dengan signifikansi 0,000 (p<0,05). Kelima, ada perbedaan social loafing pada trait kepribadian conscientiousness dengan trait kepribadian opennes dengan signifikansi 0,000 (p<0,05). Secara umum, social loafing berada pada kategori sedang. Kata kunci : social loafing, the big five personality traits Abstract. One of the negative sides of giving group assignments is the tendency of group members to reduce efforts (social loafing). Social loafing occurs due to various factors, one of which is personality. Personality is unique and consistent so that it can be used to distinguish between individuals from one another. This study aims to determine whether there are differences in social loafing in doing group assignments in terms of the big five personality traits in UNNES students.This research is a quantitative comparative research. The research sample was 414 UNNES students with the sampling technique used was proportional stratified cluster random sampling. The research data was taken using two scales, namely the social loafing scale consisting of 44 valid items with a significance level that moved from 0,000-0,044 and the scale of the big five inventory adaptation consisting of 59 valid items. Extraversion personality trait is declared valid with a significance level of 0,000, agreeableness is declared valid with a significance level of 0,000, conscientiousness is declared valid with a significance level of 0,000, neuroticism is declared valid with a significance level of 0,000, opennes is declared valid with a moving level of 0,000-0,001. The social loafing scale reliability coefficient is 0.883 and reliability on extraversion trait has a reliability coefficient of 0.851, has a reliability coefficient of 0.737, consccientiousness has a reliability coefficient of 0.853, neuroticism has a reliability coefficient of 0.796 and opennes trait has a reliability coefficient of 0.813.The analytical method used is one-way ANAVA. The results of the study indicate that there are differences in social loafing in terms of the big five personality traits. Further analysis found, first there was a difference in social loafing on the extraversion personality trait with the neuroticism personality trait with a significance of 0,000 (p <0.05). Second, there are differences in social loafing on the extraversion personality trait with the opennes personality trait with a significance of 0.006 (p <0.05). Third, there are differences in social loafing on the agreeableness personality trait with the conscientiousness personality trait with a significance of 0.010 (p <0.05). Fourth, there are differences in social loafing on the conscientiousness personality trait with the neuroticism personality trait with a significance of 0.000 (p <0.05). Fifth, there were differences in social loafing on the conscientiousness personality trait with the opennes personality trait with a significance of 0,000 (p <0.05). In general, social loafing is in the medium category. Keywords : social loafing, the big five personality traits